The effectiveness of a mobile intervention to reduce young adults’ alcohol consumption to not exceed low-risk drinking guidelines - Schulte, Mieke H.J.; Boumparis, Nikolaos; Kleiboer, Annet; Wind, Tim R.; Olff, Miranda; Huizink, Anja C.; Riper, Heleen (Frontiers in Digital Health, 2022)
Background: Young adults’ drinking habits often exceed low-risk drinking guidelines. As young adults show increased access, use, and interest in personalized content related to physical and mental well-being, mobile applications might be a suitable tool to reach this target group. This study investigates the effectiveness of ‘Boozebuster’, a self-guided mobile application incorporating various therapeutic principles to reduce young adults’ alcohol consumption to not exceeding low-risk drinking guideline levels, compared to an educational website condition. Method: Young adults aged 18-30 wanting to reduce their alcohol consumption entered a two-arm, parallel-group RCT. There were no minimum drinking severity inclusion criteria. Primary outcomes included alcohol consumption quantity and frequency. Secondary outcomes included binge drinking frequency and alcohol-related problem severity. Baseline, 6-week postbaseline, and 3-month post-baseline assessments were analyzed using linear mixed model analyses. Sex, treatment adherence, experienced engagement and motivation to change alcohol use behavior were investigated as moderators. Sub-group analyses contained problem drinkers and binge drinkers. Results: 503 participants were randomized to the intervention or control condition. Results showed no intervention effects on primary or secondary outcomes compared to the control group. Both groups showed within-group reductions on all outcomes. Sub-group analyses in problem drinkers or binge drinkers showed similar results. Motivation to change drinking behavior and experienced engagement with the application significantly moderated the intervention effect regarding the quantity or frequency of alcohol consumption, respectively. Exploratory analyses showed that participants who indicated they wanted to change their drinking patterns during the initial PNF/MI module showed a significantly greater reduction in drinking quantity compared to those who indicated not wanting to change their drinking patterns. Conclusion: The intervention group did not show a greater reduction in alcohol-related outcomes compared to the control group, but both groups showed a similar decrease. Potential explanations include similar effectiveness of both condition due to using a minimal active control in participants predominantly in the action stage of motivation to change. Future research should further explore the effectiveness of using mobile application to reduce young adults’ drinking behavior to not exceed low-risk drinking guideline levels and identify factors that motivate participants to engage with such an intervention.